A network-based approach reveals long non-coding RNAs associated with disease activity in lupus nephritis: key pathways for flare and potential biomarkers to be used as liquid biopsies - Sentis, George; Loukogiannaki, Catherine; Malissovas, Nikos; Nikolopoulos, Dionysis; Manolakou, Theodora; Flouda, Sofia; Grigoriou, Maria; Banos, Aggelos; Boumpas, Dimitrios T.; Filia, Anastasia (Frontiers in Immunology, 2023)
Objective: A blood-based biomarker is needed to assess Lupus Nephritis (LN) disease activity minimizing the need for invasive kidney biopsies. Long non-coding RNAs (lncRNAs) are known to regulate gene expression, appear to be stable in human plasma and can serve as non-invasive biomarkers. Methods: Transcriptomic data of whole blood samples from 74 LN patients and 20 healthy subjects (HC) were analyzed to identify differentially expressed (DE) lncRNAs associated with quiescent disease and flares. Weighted Gene Co-expression Network Analysis (WGCNA) was performed to uncover lncRNAs with a central role (hub lncRNAs) in regulating key biological processes that drive LN disease activity. Association of hub lncRNAs with disease activity was validated using RT-qPCR on an independent cohort of 15 LN patients and 9 HC. Cis- and trans-targets of validated lncRNAs were explored in silico to examine potential mechanisms of their action. Results: 444 DE lncRNAs were associated with quiescent disease and 6 DE lncRNAs associated with flares (FDR<0.05). WGCNA highlighted IFN signaling and B-cell activity/adaptive immunity as the most significant processes contributing to nephritis activity. Four disease-activity-associated lncRNAs, namely NRIR, KLHDC7B-DT, MIR600HG and FAM30A, were detected as hub genes and validated in an independent cohort. NRIR and KLHDC7B-DT emerged as potential key regulators of IFN mediated processes. Network analysis suggests that FAM30A and MIR600HG are likely to play a central role in the regulation of B-cells in LN through cis-regulation effects and a competing endogenous RNA mechanism affecting immunoglobulin gene expression and the IFN-λ pathway. Conclusions: The expression of lncRNAs NRIR, KLHDC7B-DT, FAM30A and MIR600HG were associated with disease activity and could be further explored as blood-based biomarkers and potential liquid biopsy on LN.